SAT0104 Comorbidity in Patients with Osteoarthritis Undergoing Hip or Knee Replacement Surgery. (10th June 2014) - Peter, W.F.; Dekker, J.; Tilbury, C.; Tordoir, R.L.; Verdegaal, S.H.; Onstenk, R.; Bénard, M.R.; Vehmeijer, S.B.; Fiocco, M.; Vermeulen, E.M.; van der Linden-van der Zwaag, H.M.; Nelissen, R.G.; et al.
Abstract : Background: In the large majority of patients with severe hip and knee osteoarthritis (OA) pain, physical functioning and quality of life improve significantly after total hip arthroplasty (THA) or total knee arthroplasty (TKA). In a subgroup of patients the outcomes are however less favorable, with comorbidity being identified as one of the contributing factors. Objectives: To describe the associations between the total number and nature of specific comorbidities, and pain, physical functioning and quality of life after THA or TKA. Methods: In this cross-sectional survey 521 patients with hip or knee OA who underwent THA (n=281) or TKA (n=240) in the previous 5-22 months were recruited from 4 hospitals. Patients' characteristics; information on comorbidities (19-item questionnaire); pain and physical functioning (subscores of the Hip disability and Knee injury Osteoarthritis Outcome Score (H/KOOS); and quality of life (SF 36 physical and mental component summary scores; PCS and MCS) were collected by means of a paper questionnaire. Descriptive statistics and multivariate regression analyses have been performed. Results: Patients'characteristics were: female 336 (65%); mean age 70.0 (SD 9.3) years; mean BMI 27.8 (SD 4.7); mean H/KOOS pain score 81.7 (SD 19.1); mean H/KOOS physical functioning score 78.9 (SD 20.9); and SF 36 PCS and MCS 45.4 (SD 8.6) and 47.7 (SD 7.7), respectively. The BMI was significantly higher, and pain and physical functioning scores were significantly worse in TKA patients than in THA patients. Overall 449 (86%) patients reported one or more comorbidities. Concerning the presence of specific comorbidities, hypertension and hearing impairments in a group conversation were the 2 most frequently reported comorbidities (>25% for the total group). Severe back pain; severe neck/shoulder pain; severe elbow, wrist or hand pain; cancer; urinary incontinence; and vision impairments were reported by 15-25% of the patients in the total group. The proportion of patients with 5 or more comorbidities was higher in patients with TKA as compared to THA (47 (20%) and 37 (13%), respectively (p=0.047)). In the total group of participants the presence of 5 or more comorbidities was significantly associated with all 4 outcomes in a multivariate regression analysis adjusting for age, sex, BMI and type of surgery (THA or TKA). Using multivariate regression models including all 19 comorbidities and the same confounders, the presence of dizziness with falling (reported by 6%) and severe back pain (reported by 19%) were each independently and significantly associated with 3 of the 4 outcomes. Conclusions: The present study showed that in patients who underwent THA or TKA, in particular the presence of 5 or more comorbidities contributes to more pain and worse physical functioning within the first 2 years after surgery. Notably, the presence of dizziness with falling and severe back pain appeared to have a considerable negative impact. These findings underline the need for a careful preoperative assessment of a large range of individual comorbidities. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3683